The Expression of Cytokine Profiles and Related Receptors in Idiopathic Inflammatory Myopathies - Zhou, Junyu; Zhao, Lijuan; Xiao, Yizhi; Xie, Shasha; Long, Ying; Wei, Yu; Meng, Qiming; Li, Xiaojing; Luo, Hui; Zhu, Honglin (Frontiers in Pharmacology, 2022)
Background: Cytokines play a vital role in the pathogenesis of idiopathic inflammatory myopathies (IIMs). Here, we investigated the expression of serum cytokine profiles in untreated IIMs and their correlations with clinical indicators, and further studied the expression of related cytokines receptors in IIMs. Methods: The Human 48-Plex Luminex assay for cytokines was performed in the serum of IIMs, including 93 untreated and 18 follow-up (39 samples) patients, and 32 healthy controls (HC). Mann-Whitney U test with bonferroni adjusted was used to identify the differentially expressed cytokines among groups. Celltalker software was used to identify the receptors of differentially expressed cytokines. The expression of receptors was further validated by published GEO datasets (muscle, blood and skin), RT-qPCR, western blot and flow cytometry. Results: The serum levels of Eotaxin, IL7, IL18, IP10, MCP1, MCSF, MIG and SCGFβ were elevated in the 93 untreated patients. Except for IL7, all other cytokines were decreased after treatment and their levels were positively correlated with clinical indices such as LDH, ESR, CRP, ALT, IgA, AST and IgG while negatively correlated with albumin and MMT8. According to the serum myositis-specific antibodies (MSAs), patients were classified into three groups: anti-ARS (Jo-1, OJ, EJ, PL7, PL12), anti-MDA5 positive, and anti-TIF1γ positive. Compared with HC, the levels of IP10 and MIG were increased in three groups. Moreover, IL18 and MSCF were increased in anti-ARS patients, and CTACK, Eotaxin, IL1Rα, IL7, IL18, MCP1, MCP3, MCSF and SCGFβ were elevated in anti-MDA5 patients. Twenty receptors of the 8 differentially expressed cytokines were matched by celltalker software, among them, IL18R1 and CCR1 were up-regulated in blood, muscle and skin of IIMs from the analysis of GEO published datasets. RT-qPCR and western blot further validated IL18R1 was upregulated in the muscle tissues of dermatomyositis. The number of IL18R1+CD4+ cells was increased while IL18R1+CD8+ cells was decreased in peripheral blood of anti-MDA5 patients. Conclusions: This study showed that cytokine profiles were significantly changed in IIMs, and different MSA groups had unique cytokine expression patterns. The levels of some cytokine were correlated with clinical indices. The IL18 receptor IL18R1 might play important roles in IIMs.